The Politics of Race and Patriarchy in Claire-Solange, âme africaine by Suzanne Lacascade - Valérie Orlando (Studies in 20th & 21st Century Literature, 2005)
Racial discrimination, colonialism, marginalization, and imperial politics are the components of Martinican author Suzanne Lacascade's 1924 novel, Claire-Solange, âme africaine. This little-known work is shrouded in mystery. Less information is available about the author or under what circumstances she conceptualized and completed her novel. Lacascade probably contributed to various reviews and journals of the first days of the Négritude movement. The novel offers one of the first discourses on race, racial mixing, hierarchy, and colonialism as construed by blacks and whites. The author defies the power of men over women in French society of the early twentieth century. Racialized parameters are synthesized, most significantly, through the protagonist Claire-Solange's views and opinions on, two environments: the first is France, whose language she speaks fluently but in which she feels foreign; and the second African, a mythical place to which she is drawn due to her African ancestry filtered through her island home of Martinique. The author offers her readers a window on the life of a mulatta woman who is caught in the middle of white and black, forced, in the end, to live in a French, beige in-between, forever considered an étrangère because of her color.
Keywords: Claire-Solange; âme africaine; Racial discrimination; colonialism; marginalization; imperial politics; Martinican author; Martinican; Suzanne Lacascade; mystery; Négritude movement; Négritude; race; racial mixing; hierarchy; black; white; constructed; identity; patriarchy; men; women; French society; French; twentieth century; France; foreign; African; African ancestry; Martinique; mulatta woman; white and black; étrangère